Mefloquine to prevent malaria: a systematic review of trials. - Croft, A. (1997)
OBJECTIVE: To evaluate the research evidence on the efficacy and tolerability of mefloquine chemoprophylaxis. SEARCH STRATEGY: Any potentially relevant trial from the Cochrane Infectious Disease Group's register of controlled trials; systematic searches of Medline, Embase, Lilacs and Science Citation Index; scanning citations; and consulting drug companies and key investigators. We considered studies in all languages. INCLUSION CRITERIA: Trials carried out in non-immune adult travellers, and in non-travelling volunteers, where an attempt had been made to conduct a randomised comparison of mefloquine against placebo or against alternative standard prophylaxis. RESULTS: 37 potentially eligible trials of mefloquine prophylaxis were identified, and 10 met the inclusion criteria. These 10 trials comprised a total of 2750 non-immune adult participants randomised to mefloquine or to a control. One placebo controlled trial examined malaria incidence directly and showed mefloquine to be highly effective in preventing malaria in an area of drug resistance. However, four placebo controlled trials showed that mefloquine was not well tolerated, and withdrawals were consistently higher in mefloquine treatment arms than in placebo arms (odds ratio 3.49 (95% confidence interval 1.42 to 8.56)). Five field trials compared mefloquine with other chemoprophylaxis. Mefloquine was no worse tolerated than other chemoprophylaxis, although there was possibly a trend towards higher withdrawals in mefloquine arms (odds ratio 1.33 (0.75 to 2.36)). CONCLUSION: One trial showed mefloquine to be effective in preventing malaria, but withdrawal rates, presumably from side effects, were high across most studies. This is likely to impair mefloquine's effectiveness in general travellers, and it may therefore not be useful for routine prophylaxis. Mefloquine may be useful in specific situations such as for groups travelling to regions with a high risk of chloroquine resistant malaria and only limited access to effective medical care.